Efektivitas Pelatihan Efikasi Diri (Self Efficacy) Untuk Menurunkan Kejenuhan Kerja Pada Guru SLB YSCL Bandar Lampung - Ngatemi; Tansri Adzlan Syah; Khairani (PSIKOLOGI KONSELING, 2025)
Teachers in Special Education Schools (SLB), such as YSCL Bandar Lampung, face significant challenges in educating students with special needs. High workloads, performance demands, and limited support often lead to increased levels of job burnout. This study aims to examine the effectiveness of self-efficacy training in reducing job burnout and enhancing educational quality in the special education context. A quasi-experimental design with a one-group pretest-posttest approach was used. Participants were selected using the saturated sampling technique. Data was collected using the Maslach Burnout Inventory (MBI) and the Teachers’ Sense of Efficacy Scale (TSES). Data analysis was performed using paired t-tests, ANOVA, and regression to assess the impact of the training on teacher self-efficacy and burnout. Pretest results showed that 70% of teachers experienced moderate burnout, 20% mild burnout, and 10% severe. After the intervention, the rate of mild burnout increased to 35%, moderate burnout was 65%, and there were no longer any teachers experiencing severe burnout. Following the intervention, the proportion of teachers reporting mild burnout. increased to 35%, while no teachers remained in the severe category. The burnout score also showed a significant reduction from 60.65 to 53.20 (t = 3.308; p = 0.004), indicating the effectiveness of the self-efficacy training program. These results support the integration of self-efficacy training into professional development programs for special education teachers. Schools and education authorities are encouraged to adopt similar interventions to improve teacher well-being and resilience, particularly in inclusive and high-demand educational environments.